IL-33 Gene Polymorphisms as Potential Biomarkers of Disease Susceptibility and Response to TNF Inhibitors in Rheumatoid Arthritis, Ankylosing Spondylitis, and Psoriatic Arthritis Patients - Iwaszko, Milena; Wielińska, Joanna; Świerkot, Jerzy; Kolossa, Katarzyna; Sokolik, Renata; Bugaj, Bartosz; Chaszczewska-Markowska, Monika; Jeka, Sławomir; Bogunia-Kubik, Katarzyna (Frontiers in Immunology, 2021)
Objective: Rheumatoid arthritis (RA), ankylosing spondylitis (AS) and psoriatic arthritis (PsA) belong to inflammatory rheumatic diseases, the group of conditions of unknown etiology. However, strong genetic component in their pathogenesis has been well established. A dysregulation of the cytokine network plays an important role in the development of the inflammatory arthritis. The interleukin 33 (IL-33) is a recently identified member of the IL-1 family. The significance of the IL‑33 in the inflammatory arthritis has been poorly studied to date. The aim of this research was to investigate a potential of IL-33 gene polymorphisms to serve as biomarkers in disease susceptibility and therapeutic response in RA, AS and PsA patients treated with TNF inhibitors. Materials and Methods: In total, 735 patients diagnosed with RA, AS, PsA and 229 healthy individuals were enrolled to the study. Genotyping for 3 single nucleotide polymorphisms (SNPs) within the IL-33 gene: rs16924159 (A/G), rs10975519 (T/C), rs7044343 (C/T) was performed using a polymerase chain reaction amplification employing LightSNiP assays. Results: In the present study the IL-33 rs10975519 CC genotype was associated with decreased risk of RA development among females. Furthermore, the IL-33 rs16924159 polymorphism was found to be associated with an efficacy of anti-TNF therapy as well as clinical parameters in RA and AS patients. Presence of the IL-33 rs16924159 AA genotype correlated with higher disease activity and worse clinical outcome in RA patients treated with TNF inhibitors. Also, AS patients carrying the IL-33 rs16924159 AA genotype had higher disease activity and displayed worse response to anti-TNF therapy. That indicates a deleterious role of the IL-33 rs16924159 AA genotype in context of RA as well as AS. Conclusions: The obtained results suggest that IL-33 gene polymorphisms might be potential candidate biomarkers of the disease susceptibility and anti-TNF treatment response in patients with inflammatory rheumatic diseases.